From Ideal to Reality: Constitutional Engineering of the XXI Century - ABRAMOVA, Marianna; POPOVA, Anna; VASILIEVA, Oxana; MILOVANOVA, Marina; POLISHCHUK, Nikolay (Journal of Advanced Research in Law and Economics; Vol 8 No 3 (2017): JARLE Volume VIII Issue 3(25) Summer 2017, 2017)
In this article the author suggests his own point of view on the problem of constitutional engineering for the modern level of constitutional and legal development of Russia. The authors suggest to evaluate the opportunities of the legal reform from the perspective of construction methods of state-legal ideal in the politico-legal idea of Western Europe and Russia.